Optimizing Retrieval of Biospecimens Using the Curated Cancer Clinical Outcomes Database (C3OD). (November 2019) - Mudaranthakam, Dinesh Pal; Shergina, Elena; Park, Michele; Thompson, Jeffrey; Streeter, David; Hu, Jinxiang; Wick, Jo; Gajewski, Byron; Koestler, Devin C; Godwin, Andrew K; Jensen, Roy A; Mayo, Matthew S
To fully support their role in translational and personalized medicine, biorepositories and biobanks must continue to advance the annotation of their biospecimens with robust clinical and laboratory data. Translational research and personalized medicine require well-documented and up-to-date information, but the infrastructure used to support biorepositories and biobanks can easily be out of sync with the host institution. To assist researchers and provide them with accurate pathological, epidemiological, and bio-molecular data, the Biospecimen Repository Core Facility (BRCF) at the University of Kansas Medical Center (KUMC) merges data from medical records, the tumor registry, and pathology reports using the Curated Cancer Clinical Outcomes Database (C3OD). In this report, we describe the utilization of C3OD to optimally retrieve and dispense biospecimen samples using these 3 data sources and demonstrate how C3OD greatly increases the efficiency of obtaining biospecimen samples for the researchers.